Judgment of Gender through Facial Parts. (November 2013) - Yamaguchi, Masami K; Hirukawa, Tastu; Kanazawa, So
Japanese male and female undergraduate students judged the gender of a variety of facial images. These images were combinations of the following facial parts: eyebrows, eyes, nose, mouth, and the face outline (cheek and chin). These parts were extracted from averaged facial images of Japanese males and females aged 18 and 19 years by means of the Facial Image Processing System. The results suggested that, in identifying gender, subjects performed identification on the basis of the eyebrows and the face outline, and both males and females were more likely to identify the faces as those of their own gender. The results are discussed in relation to previous studies, with particular attention paid to the matter of race differences.